Synthesis and reactivity of [PCCP]-coordinated group 5 alkyl and alkylidene complexes featuring a metallacyclopropene backbone - Federmann, Patrick; Wadepohl, Hubert; Ballmann, Joachim (Organometallics, 2019)
The R2P-functionalized tolanes 1a (R = Ph) and 1b (R = iPr) were employed for the synthesis of [PCCP]-coordinated group 5 complexes. In the case of vanadium, the d1-configured dialkyl species [PCCP]V(CH2SiMe3)2 (3a and 3b) were prepared and found to be resistant toward oxidation, i.e., the corresponding alkylidene complexes were not observed upon treatment with various oxidants. For niobium and tantalum, however, the high-valent d0-configured alkyl-alkylidene complexes [PCCP]M(=CHSiMe3)(CH2SiMe3) (M = Nb: 6b, M = Ta: 7b) were obtained for the iPr2P-substituted ligand. Both these alkylidenes, i.e., 6b and 7b, were employed for ring-opening metathesis polymerizations (ROMP) of strained olefins. Although the η2-alkyne motifs in 6b and 7b are best described as metallacyclopropenes, the unsaturated ligand backbone was neither degraded nor copolymerized over the course of these polymerizations. Upon hydrogenolysis of 7b, however, the metallacyclopropene backbone was partially hydrogenated, and the dinuclear (μ-H)3-bridged tantalum(V) complex 8 featuring a metallacyclopropane substructure was formed. An intermediate in this reaction was shown to catalytically hydrogenate one or both arenes in naphthalene, while the isolated dimeric species 8 was found to be inactive under identical reaction conditions.
Gesehen am 13.12.2019